A Far African Arrt. - Van Tendeloo, Gery; Delrue, Henk; Magnin, André; Hoet, Jan (s.l. : s.n., 1990)
Isek Kingelez, Bodys ; Ekefrey, Emmanuel ; Bruly Bouabre, Frederic ; Cheick-Ledy ; Moke ; Kwei, Kane ; Unya, Chief Mark ; Fundi, John ; Kossi, Agbagli ; Camara, Seni Awa ; Amidou, Dossou ; MuTwins Seven Seven ; Efiaimbelo
WAAAAW, A Far African Arrt, Kortrijk, 1990
boek